Description of the freeliving marine nematode Dracognomus tinae n. sp. (Draconematoidea: Prochaetosomatidae). - Jensen, P (Cah. Biol. mar., 1981)
Locality: ; Cabinet:n1591
from NeMys; NeMys doc_id: 6697